Pembelajaran Model Cooperative Learning Tipe TAI untuk Meningkatkan Hasil Belajar Akuntansi - Mardiyanti Mardiyanti (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research is motivated by the low learning outcomes of accounting in class XI AKL 3 at SMK Negeri 1 Depok. The aim of the research is to find out the increase in student learning outcomes after using the TAI type of cooperative learning model. This research is a Classroom Action Research which took place in July–September 2022. The research subjects were 36 students. The research object is the process of implementing learning with the cooperative learning model type TAI. The instruments in this study were lesson plans assessment sheets, observation sheets and test questions. The research procedure was carried out in two cycles, cycle I consisting of 4 meetings and cycle II consisting of 3 meetings. The results showed that the application of the TAI type of cooperative learning could improve accounting learning outcomes at SMK Negeri 1 Depok. The increase in student learning outcomes is marked by an increase in the number of students who achieve scores above the Minimum Completeness Criteria (KKM). This can be seen from the average value of learning outcomes in pre-cycle 64 which increased in cycle I and cycle II, namely 78.61 and 83.33. In addition to grades, KKM achievement also increased from 36.11% in pre-cycle to 66.67% in cycle I and 89.89% in cycle II.